2019
DOI: 10.3349/ymj.2019.60.10.924
|View full text |Cite
|
Sign up to set email alerts
|

microRNA-146a Promotes Growth of Acute Leukemia Cells by Downregulating Ciliary Neurotrophic Factor Receptor and Activating JAK2/STAT3 Signaling

Abstract: PurposeAcute leukemia (AL) is classified as acute lymphoblastic leukemia (ALL) and acute myeloid leukemia (AML). This study aimed to investigate the effect of miR-146a on childhood AL and its underlying molecular mechanisms.Materials and MethodsBone marrow samples were obtained from 39 AL children and 10 non-cancer controls. The expressions of miR-146a and ciliary neurotrophic factor receptor (CNTFR) were detected by quantitative real-time polymerase chain reaction (qRT-PCR) in ALL and AML pediatric patients, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 38 publications
(43 reference statements)
2
20
0
Order By: Relevance
“…We conducted in-depth KEGG and GO pathway enrichment analyses of the genes corresponding to the nine Hyper-DMPs and one Hypo-DMP, and we analyzed their protein-protein interactions in the STRING database. The leukemia inhibitory factor signaling pathway and the ciliary neurotrophic factor-mediated signaling pathway, both of which can activate the JAK2/STAT3 signaling pathway [ 34 , 35 ], were found to be enriched in our GO analysis. Coincidentally, the JAK/STAT pathway was found to be enriched in our KEGG pathway analysis.…”
Section: Discussionmentioning
confidence: 99%
“…We conducted in-depth KEGG and GO pathway enrichment analyses of the genes corresponding to the nine Hyper-DMPs and one Hypo-DMP, and we analyzed their protein-protein interactions in the STRING database. The leukemia inhibitory factor signaling pathway and the ciliary neurotrophic factor-mediated signaling pathway, both of which can activate the JAK2/STAT3 signaling pathway [ 34 , 35 ], were found to be enriched in our GO analysis. Coincidentally, the JAK/STAT pathway was found to be enriched in our KEGG pathway analysis.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, many scientists have focused on the roles of non-coding RNAs in AML development and therapy, including microRNAs (miRNAs) and long noncoding RNAs (lncRNAs) [5]. MiRNAs are a class of single-stranded small non-coding RNAs with 19-22 nucleotides in length, which modulate gene expression at the post-transcriptional level via binding to the 3 ā€²untranslated regions of target genes [6]. Some studies found that microRNA-14a (miR-146a) was downregulated in some AML patients [7][8][9], which suggested miR-146a played a critical pathogenic role in AML.…”
Section: Introductionmentioning
confidence: 99%
“…And we found that rs2910164 G allele might confer risk to DSC. A previous study identified that the expression of miR-146a promoted in acute myeloid leukemia and acute lymphoblastic leukemia cases (Wang et al 2019). As well, Khorrami et al suggested that the higher level of miR-146a was importance for the milieu of immune suppression and drug-resistant CRC cells (Khorrami et al 2017).…”
Section: Discussionmentioning
confidence: 94%